ANALISIS KINERJA KEUANGAN MENGGUNAKAN METODE EVA PADA PERUSAHAAN PELAYARAN SEKTOR ENERGI YANG TERDAFTAR DI BEI PERIODE 2019-2022 - Fadhlina, Fadhlina; Hardi, Enny; Novriyandana, Rifqi (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2024)
Abstract, This study aims to determine and analyze financial performance using the Economic Value Added (EVA) method in energy sector shipping companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2022 period. This type of research is qualitative with a descriptive approach. The population in this study were energy sector shipping companies listed on the Indonesia Stock Exchange (IDX) totaling 19 companies. The sample in this study were 13 companies determined by purposive sampling method. The type of data used is secondary data. The results showed that financial performance using the Economic Value Added (EVA) method in energy sector shipping companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2022 period fluctuated. The occurrence of the COVID-19 pandemic and the decline in demand for oil, gas and coal transportation made the company experience a decrease in revenue. Nevertheless, the company continues to strive to improve its performance by implementing and planning strategies and policies to be better in the future.